2018
DOI: 10.1002/iub.1742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histone deacetylase inhibitor on epithelial‐mesenchymal transition of liver fibrosis

Abstract: Liver fibrosis is an excessively reversible wound healing process and the fibrotic disorder is the activation of hepatic stellate cell that requires extensive alterations in gene expression. As reversible deacetylation of histone proteins modulate gene expression, we examined the effect of valproic acid (VPA) as selective histone deacetylase inhibitor on CCl-4 induced liver fibrosis. Thirty rats were divided into three equal groups; control group, fibrotic group and VPA-treated group. The rats were sacrificed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In addition to the ECM products, myofibroblasts also synthesize α-smooth muscle actin (α-SMA) (49). Ramzy et al indicated that an increase in α-SMA marks the activation of HSCs (50).…”
Section: From Nash To Liver Fibrosismentioning
confidence: 99%
“…In addition to the ECM products, myofibroblasts also synthesize α-smooth muscle actin (α-SMA) (49). Ramzy et al indicated that an increase in α-SMA marks the activation of HSCs (50).…”
Section: From Nash To Liver Fibrosismentioning
confidence: 99%
“…Even though valproate (VPA) and its sodium salt, sodium valproate, can inhibit class II HDACs, they also strongly suppress class I HDACIs [ 29 , 127 ]. Sodium valproate has been well established as a long-term therapy of epilepsy, which attests to the safety of this molecule when chronically administered in humans, at least in patients without preexisting liver conditions [ 127 , 128 ]. However, it has also been proposed as a treatment for liver fibrosis by several experimental studies, therefore expanding its clinical applications ( Figure 2 ).…”
Section: Hdac Inhibitors As Therapeutic Tools To Treat Liver Fibromentioning
confidence: 99%
“…VPA is able to significantly reduce S. mansoni -induced fibrosis and inflammation through downregulation of profibrogenic factors and collagen deposition [ 131 ]. VPA antifibrogenic properties were corroborated in an in vivo rat model of CCl 4 -induced fibrosis, which were characterized by α-Sma downregulation, circulating AST and ALT reduction and decreased collagen deposition [ 127 ]. Although compelling evidences support the promising effects of HDACIs in liver fibrosis, the underlying mechanisms are still not well known.…”
Section: Hdac Inhibitors As Therapeutic Tools To Treat Liver Fibromentioning
confidence: 99%
“…Some studies of animal models have shown that inhibitors of HDAC such as trichostatin A (TSA) and valproic acid (VPA) significantly decrease the level of Smad3/Smad4 complexes in TGF-β1/Smad signaling of fibroblasts that rely on the epigenetic modulation of collagen I type. 26 , 27 Choi et al 28 showed that in a mouse model of unilateral ureteral obstruction (UUO), CG200745, an inhibitor of HDAC attenuated oxidative stress, inflammatory cytokines and also markedly reduced the expression of α-SMA, fibronectin, collagen I, and TGF-β. Choi et al 29 showed that the overexpression gene of Smad7 inhibited the TGF-β1 induced production of ECM, myofibroblastic differentiation of PD-derived fibroblasts, phosphorylation, and nuclear translocation of Smad2/3.…”
Section: Introductionmentioning
confidence: 99%